The power of parables essays on the comparative study of Jewish and Christian parables - Power of Parables: Narrative and Religious Identity in Late Antiquity 2019 Utrecht; Ottenheijm, Eric 1961-; Poorthuis, Marcel 1955-; Merz, Annette 1965- (Leiden Boston Brill, 2024)
"The Power of Parables documents the surprising ways in which Jewish and Christian parables bridge religion with daily life. This 2019 conference volume rediscovers the original power of parables to shock and affect their audience, which has since been reduced by centuries of preaching and repetition. Not only do parables enhance the perspective on Scripture or the kingdom of heaven, they also change the sensory regime of the audience in perceiving the outer world. The theological differences in their applications appear secondary in view of their powerful rhetoric and suggest a shared genre"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Parables -- Congresses; Storytelling -- Religious aspects -- Judaism -- Congresses; Storytelling -- Religious aspects -- Christianity -- Congresses; Konferenzschrift -- 2019 -- Utrecht; Aufsatzsammlung